The Role of Composing the Soundtrack for the Dramatic Film (Psychopath): An Analytical Study - misanjas, misanjas; Mohammad Mustafa, Seerwan; Mustafa Ibrahim, Abdulnaser ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The current research on composing film scores for dramatic films is an aesthetically and functionally complementary element in dramatic structure, achieved through the mental and emotional interaction between the components of cinematic language. It serves as a purposeful window for conveying sensory and cognitive effects through melody and rhythm, facilitating the organization and coordination between image and sound, In extracting meaning and analyzing the film’s approach and direction through symbols, signals, and both direct and suggestive meanings, it becomes a form of artistic language that is understandable, perceptible, and open to interpretation as envisioned by the director for their film, allowing the depth of meaning to reach the audience, The researchers believe that the current study titled "The Role of Soundtrack Composition in the Dramatic Film Psychopath: An Analytical Study" is a qualitative artistic experience that adopts a content analysis approach for practical application. The research problem is as follows: What is the role of soundtrack composition in the dramatic film? The study follows a content analysis methodology for the research sample Psychopath.